Bridging the Gap in Understanding the Mechanism of NH 3 Formation During NO Reduction by CO in the Presence of H 2 O Over Rh/Al 2 O 3 Catalysts: DFT Study - Chanthip Wangphon; Patcharaporn Khajondetchairit; Meena Rittiruam; Annop Ektarawong; Björn Alling; Rathawat Daengngern; Piyasan Praserthdam; Tinnakorn Saelee; Supareak Praserthdam (Advanced Theory and Simulations, 2026)
ABSTRACT Ammonia (NH 3 ) formation from nitric oxide (NO) and carbon monoxide (CO) in the presence of water is a promising pathway for low‐temperature NO x reduction. In this work, density functional theory (DFT) calculations were used to investigate the mechanism of NH 3 formation on a Rh(111)/γ‐Al 2 O 3 (110), in which the Rh(111) and γ‐Al 2 O 3 (110) were considered separately. NO readily dissociates on the Rh site, forming N*, which reacts with CO to produce the key intermediate of NCO*. Meanwhile, water dissociates more easily on γ‐Al 2 O 3 (110), providing H* species. The hydrolysis of NCO* can proceed via two pathways: on Rh(111), it forms HNCO, while on γ‐Al 2 O 3 (110), it forms HNCOH*. Both intermediates subsequently decompose into NH* species, which are then hydrogenated to produce NH 3 . The Rh pathway is more favorable in both kinetics and thermodynamics, while the support mainly supplies hydrogen through water activation. These results suggest a dual‐site mechanism in which Rh drives the main transformation, and γ‐Al 2 O 3 (110) assists via hydrogen transfer. This work presents the individual roles of Rh and Al 2 O 3 surfaces in NO reduction with CO, producing NH 3 , which is relevant to catalytic behavior under humid conditions.
Keywords: Ammonia Synthesis and Nitrogen Reduction; Catalytic Processes in Materials Science; Advanced Chemical Physics Studies